Pemberian PupukOrganikHayatiGreen BotanedanRock Phosphatepada Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Fase Pembibitan Utama di Medium Ultisol - Ferdinand M. P Simatupang; Yunel Venita; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research was conducted at the experimental farm of the Faculty of Agriculture, University of Riau, Pekanbaru 12.5 Km Binawidya Campus from April to July 2016. Trial usingcompletely randomized design (CRD) factorial. The first factor utilization of organic fertilizer biological Green Botane consisted of 4 levels (0, 25, 50, and 75) g/ polybag plants and the second factor of fertilizers Rock Phosphate consisting of 3 levels (15, 30, and 45) g/polybag plants. The treatment was repeated 3 times. Data results were analyzed statistically operates with ANOVA andcontinued test of HSD (Honestly Significant Difference) at 5% level. The observed parameters isplant high, leaf number, diameter stump, root volume, the ratio of the canopy and root dry weight and analysis of plant phosphor uptake. Results indicate the interaction of biological organic fertilizer Green Botane and Rock Phosphate significant effect on the root volume, dry weight and the ratio of the canopy and roots, no real effect on the increase of high growth, leaf number, diameter core and analysis of phosphorus uptake. The combination of biological organic fertilizer Green Botane 75 g/polybag and Rock Phosphate 45 g/polybag is the best combination of the parameters and increase plant growth tends to increase. Keywords:Elaeisguineensis Jacq., biological organic fertilizers, Rock phosphate, Ultisol